2016
DOI: 10.1002/etc.3574
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, distribution in different tissues, and genotoxicity of imidacloprid in the freshwater fish Australoheros facetus

Abstract: The neonicotinoid imidacloprid is under re-evaluation by regulatory agencies because of the poor current information available regarding its potential effects. One of the goals of the present study was to determine imidacloprid uptake and distribution in the freshwater fish Australoheros facetus experimentally exposed for 24 h and 48 h to 100 μg/L, 300 μg/L, and 2500 μg/L. The toxicity of imidacloprid to fish reported in the literature is in the milligrams per liter or gram per liter range, but sublethal effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 52 publications
2
21
1
3
Order By: Relevance
“…Similar genotoxic and cytotoxic effects occurred in carp Cyprinus carpio and silver catfish Rhamdia quelen exposed to fipronil (Qureshi et al 2016;Menezes et al 2016). Genotoxic effects were also observed in chameleon cichlids Australoheros facetus exposed to imidacloprid (Iturburu et al 2017). …”
Section: Sublethal Effectssupporting
confidence: 53%
“…Similar genotoxic and cytotoxic effects occurred in carp Cyprinus carpio and silver catfish Rhamdia quelen exposed to fipronil (Qureshi et al 2016;Menezes et al 2016). Genotoxic effects were also observed in chameleon cichlids Australoheros facetus exposed to imidacloprid (Iturburu et al 2017). …”
Section: Sublethal Effectssupporting
confidence: 53%
“…GST protects cells from the deleterious effects of toxic end products of lipid peroxidation. Therefore, increased or unchanged GST activity is considered to be one of the mechanisms that prevent oxidative stress [30]. Similar to the results of this study, Wu et al, reported that imidacloprid induced GST activity in zebrafish embryos [23].…”
Section: Biochemical Responsessupporting
confidence: 88%
“…Acute pathogenicity was determined calculating the lethal dose 50% in 96 hr (LD50 96 ) through the experimental challenge of Australoheros facetus (Pisces: Cichlidae), proceeded from the Instituto de Investigaciones Pesqueras of Universidad de la República (1.5 g of mean body weight). This is a fish species widely distributed in the region and developed in laboratory for use in different types of experimental challenges (Crupkin et al., ; Iturburu et al., ). Five different concentrations (1:10 dilutions from 10 9 CFU/fish) of bacterial suspensions in sterile PBS were evaluated by intraperitoneal injection of 10 μl.g‐1 of body weight.…”
Section: Methodsmentioning
confidence: 99%